Status of micronutrients and their relation with cognition level among children with attention deficit hyperactivity disorder (BIRDEM Medical Journal, 2025)
Background: Attention deficit hyperactivity disorder (ADHD) is a prevalent, multifactorial and highly hereditary neuropsychiatric disorder affecting 8-12% of children globally, characterized by inattention, hyperactivity, impulsivity and cognitive impairments. Poor dietary habits contribute to nutritional imbalances, which potentially worsen ADHD symptoms, emphasizing the importance of nutrition management in treatment. This study aimed to explore any nutritional imbalances in children with ADHD and evaluate their cognitive levels, which could have significantly supported their treatment. Methods: The study was an observational one, done in 2020, involving 63 participants (43 ADHD cases and 20 healthy controls). The ADHD cases were children, aged 1–18 years from the outpatient department (OPD) of the Institute of Paediatric Neurodisorder and Autism (IPNA) at Bangabandhu Sheikh Mujib Medical University (BSMMU), diagnosed based on DSM-5 criteria. The control group consisted of healthy children from Kazipara, Dhaka matched for age and socio-economic status. After selection, blood samples were collected and analyzed for zinc, magnesium, iron and vitamin D levels at the BSMMU biochemistry laboratory. An assigned psychologist assessed the cognitive levels of the participants. Results: For ADHD children, serum zinc level (M±SD) was 100.30±31.24 micro-g/dl, magnesium level was 1.98±.54 mg/dl, iron level was 59.30±24.09 micro-g/dl and vitamin D was 22.09±6.90 ng/dl. Among ADHD children, 14% had serum zinc levels below the normal range, whereas 10% of normal children had below normal zinc levels. Surprisingly, 37% of ADHD children had serum zinc levels above the normal range. Regarding serum magnesium, 12% of ADHD children had levels below normal, while 10% of normal children had levels above normal. For serum iron, 70% of ADHD children had below normal levels, compared to 35% of normal children. Regarding serum vitamin D, only 9% of ADHD children had levels below the normal range, whereas 35% of normal children had low levels. A significant association was found between low IQ levels and low serum vitamin D levels, when Vit D level. Other micronutrients did not have any association with congnitive levels. Conclusion: The study found that children with ADHD had different plasma concentrations of zinc, magnesium, iron and vitamin D compared to typically developing children. There was significant association between low IQ level and vitamin D but not with other micronutrients. BIRDEM Med J 2025; 15(3): 98-102